2021
DOI: 10.1002/eqe.3549
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the damage accumulation of reinforced concrete columns under mainshock‐aftershock sequences

Abstract: This paper presents the details and results of shaking table tests conducted on six 1/3‐scaled reinforced concrete columns subjected to mainshock‐aftershock (MSAS) ground motions. For each of the two subsets distinguished by the axial compression ratio in the test matrix, one column specimen was subjected to a standard cyclic loading protocol, whereas the second specimen was subjected to a mainshock ground motion record followed by a standard cyclic loading protocol. The third specimen was subjected to MSAS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The results showed that uncertainty in the vulnerability under the main shock and mainshock-aftershock sequence was greater than the uncertainty in the vulnerability under the main shock. Sun et al 13 conducted shaking table tests on six reinforced concrete columns under the action of mainshock-aftershock sequences. The results indicated that compared with the case where only the main shock occurred, the aftershock further reduced the structural strength and stiffness of the specimens by 9% and 7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that uncertainty in the vulnerability under the main shock and mainshock-aftershock sequence was greater than the uncertainty in the vulnerability under the main shock. Sun et al 13 conducted shaking table tests on six reinforced concrete columns under the action of mainshock-aftershock sequences. The results indicated that compared with the case where only the main shock occurred, the aftershock further reduced the structural strength and stiffness of the specimens by 9% and 7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that uncertainty in the vulnerability under the main shock and mainshock‐aftershock sequence was greater than the uncertainty in the vulnerability under the main shock. Sun et al 13 . conducted shaking table tests on six reinforced concrete columns under the action of mainshock‐aftershock sequences.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of correlation between the maximum displacement deformation of the structure and the earthquake duration [13], but there is a good correlation between the earthquake duration effect and the accumulated hysteretic energy of the structure under the earthquake actions [14]. With the intensification of the decay process, the correlation between the earthquake duration effect and the accumulated hysteretic energy is higher [15].…”
Section: Introductionmentioning
confidence: 99%
“…Displacement-based and bearing-capacity-based seismic design methods can reflect the amplitude and frequency characteristics of earthquakes, but fail to consider the impact of earthquake duration on structures. [1][2][3][4] The energy-based seismic design method not only reflects the displacement deformation and bearing capacity, but also considers the cumulative energy dissipation damage caused by the earthquake duration, [5][6][7][8][9] which can fully reflect the impact of earthquake action on the structure.…”
Section: Introductionmentioning
confidence: 99%